The Mother of the Gods, Athens, and the tyranny of Asia : a study of sovereignty in ancient religion - Munn, Mark Henderson (Joan Palevsky imprint in classical literature., 2006)
Among maternal deities of the Greek pantheon, the Mother of the Gods was a paradox. Conflict and resolution were played out symbolically, Munn shows, and the goddess of Lydian tyranny was eventually accepted by the Athenians as the Mother of the Gods and a symbol of their own sovereignty.